Case files. Pharmacology - Eugene C. Toy
Real-life clinical cases for the basic sciences and USMLE step 1. Experience with clinical cases is key to excelling on the USMLE Step 1 and shelf exams, and ultimately to providing patients with competent clinical care. Case Files: Pharmacology provides 56 true-to-life clinical cases that illustrate essential concepts in pharmacology. Each case includes an easy-to-understand discussion correlated to key basic science concepts, definitions of key terms, pharmacology pearls, and USMLE-style review questions. With Case Files, you'll learn instead of memorize. You can learn from 56 high-yield cases, each with board-style questions. You can master key concepts with clinical pearls. You can polish your approach to clinical problems and to patient care. You can maximize your board scores with the proven Case Files system